LAMOST observations in the Kepler field - De Cat P.; Fu J.N.; Yang X.H.; Ren A.B.; Frasca A.; Molenda-Żakowicz J.; Catanzaro G.; Gray R.O.; Corbally C.J.; Shi J.R.; Zhang H.T.; Luo A.L. (EPJ Web of Conferences, 2015)
The Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) at the Xinglong observatory in China is a new 4-m telescope equipped with 4,000 optical fibers. In 2010, we initiated the LAMOST-Kepler project. We requested to observe the full field-of-view of the nominal Kepler mission with the LAMOST to collect low-resolution spectra for as many objects from the KIC 10 catalogue as possible. So far, 12 of the 14 requested LAMOST fields have been observed resulting in more than 68,000 low-resolution spectra. Our preliminary results show that the stellar parameters derived from the LAMOST spectra are in good agreement with those found in the literature based on high-resolution spectroscopy. The LAMOST data allows to distinguish dwarfs from giants and can provide the projected rotational velocity for very fast rotators.